2023
DOI: 10.1021/acs.inorgchem.3c01884
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Sponge Behavior in a Two-Dimensional Rare-Earth Hybrid Coordinate Polymer

Ze-Jiang Xu,
Na Wang,
Wang Luo
et al.

Abstract: Stimuli-responsive multifunctional materials (SRMMs) have attracted tremendous attention due to their dynamic responses to external stimuli. However, it remains challenging to simultaneously achieve solvent-induced single-crystal to single-crystal (SCSC) transformation and structural phase transition after desolvation. Here, we report a two-dimensional (2D) rare-earth organic-inorganic hybrid coordinate polymer [(CH3)3NCH2Cl]2[Eu·H2O]2[CH2(SO3)2]4·2H2O (1) that exhibits a reversible SCSC transformation by chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Organic–inorganic hybrid perovskite (OIHPs) materials have wide potential applications in intelligent device fields such as information storage, shape memory, actuators, and X-ray radiation detection, etc. On account of they behave the features of an easy synthesis process, tunable structure, and excellent performance. To date, OIHPs have become a good platform to develop a large family of functional materials, such as ferroelectrics, piezoelectrics, ferroelastics, and photoelectric detectors, etc. Similar to ferroelectricity and ferromagnetism, the nonlinear force hysteresis loop characteristic of the inherent spontaneous strain by mechanical force is defined as ferroelasticity. , The response of spontaneous strain orientation to force, light, and thermal stimuli provides potential applications of ferroelastics in mechanical switches, optical domain wall memories, pressure sensors, etc. Notably, recent studies have shown that the ferroelastic domain walls of OIHPs contributing to microscopic carrier transport. ,, Therefore, the introduction of ferroelasticity into semiconductor materials may help to enhance the photoelectric detection property. However, 2D OIHPs ferroelastic crystals with an X-ray radiation current response have hardly been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Organic–inorganic hybrid perovskite (OIHPs) materials have wide potential applications in intelligent device fields such as information storage, shape memory, actuators, and X-ray radiation detection, etc. On account of they behave the features of an easy synthesis process, tunable structure, and excellent performance. To date, OIHPs have become a good platform to develop a large family of functional materials, such as ferroelectrics, piezoelectrics, ferroelastics, and photoelectric detectors, etc. Similar to ferroelectricity and ferromagnetism, the nonlinear force hysteresis loop characteristic of the inherent spontaneous strain by mechanical force is defined as ferroelasticity. , The response of spontaneous strain orientation to force, light, and thermal stimuli provides potential applications of ferroelastics in mechanical switches, optical domain wall memories, pressure sensors, etc. Notably, recent studies have shown that the ferroelastic domain walls of OIHPs contributing to microscopic carrier transport. ,, Therefore, the introduction of ferroelasticity into semiconductor materials may help to enhance the photoelectric detection property. However, 2D OIHPs ferroelastic crystals with an X-ray radiation current response have hardly been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Organic–inorganic hybrid materials (OIHMs) have attracted broad attention to exploring multiferroic materials due to their easy structural diversity and tunability, mild preparation conditions, and easy film-forming. In particular, the inherent characteristic of OIHMs is the targeted design and performance optimization at the molecular level . As is well known, molecular ferroelectrics require a polar structure and symmetry breaking.…”
Section: Introductionmentioning
confidence: 99%